2021
DOI: 10.1002/lio2.569
|View full text |Cite
|
Sign up to set email alerts
|

The new “cubism” graft technique in tympanoplasty: A randomized controlled trial

Abstract: Objectives The aim of this prospective, randomized‐controlled study is to analyze the outcomes of a new graft technique in tympanoplasty and compare its outcomes with cartilage island graft plus extra perichondrium. Methods A total of 44 patients with noncomplicated chronic otitis media were included in this prospective randomized‐controlled clinical trial. Patients were randomly divided into 2 double‐layer graft groups: The cartilage island graft + cubism graft (study group) and the cartilage island graft + e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Cubism graft group was significantly higher than Temporalis fascia only group regarding ABG gain 3 month (p= 0.005). In agreement with the present study Kaya et al, 2021 found that there was no statistically significant difference in the preoperative ABG between study and control groups (P > .05). There were statistically significant differences in the postoperative first month ABG and ABG gain between study and control groups (P < .001).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Cubism graft group was significantly higher than Temporalis fascia only group regarding ABG gain 3 month (p= 0.005). In agreement with the present study Kaya et al, 2021 found that there was no statistically significant difference in the preoperative ABG between study and control groups (P > .05). There were statistically significant differences in the postoperative first month ABG and ABG gain between study and control groups (P < .001).…”
Section: Discussionsupporting
confidence: 92%
“…The current study was in line with the study by Kaya et al, 2021 aimed to analyze the outcomes of a new graft technique in tympanoplasty and compare its outcomes with cartilage island graft plus extra perichondrium. The study included 44 patients were randomly divided into 2 double-layer graft groups: The cartilage island graft + cubism graft (study group) and the cartilage island graft + extra perichondrium (control group).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…TM perforation is now treated with tissue adhesive-based myringoplasty, which is seen as a cutting-edge method (Azimi B et al, 2021). Since the 1980s, tissue adhesives have been used in ear surgery to hold the graft in place during tympanoplasty, act as scaffolding while vascularization takes place, and keep the area dry to prevent infection (Kaya et al, 2021). Research has shown that tissue adhesives help grafts take hold better (Bansal C et al,2020).…”
Section: Introductionmentioning
confidence: 99%